Does Hearing Loss in the Elderly Individuals Conform to Impairment of Specific Cognitive Domains?. (July 2020) - Guglielmi, Valeria; Marra, Camillo; Picciotti, Pasqualina M.; Masone Iacobucci, Giovanna; Giovannini, Silvia; Quaranta, Davide; Anzivino, Roberta; Paludetti, Gaetano; Conti, Guido
Background: It is well known that age-related hearing loss (ARHL) is strongly associated with dementia. Different hypotheses have been considered to explain this link, including sensorial deprivation, the reduction in cognitive reserve, and the presence of shared pathological pathways (microvascular damage of the brain). Aims: We carried out a study of the audiological and neuropsychological characteristics of a sample of hearing impaired but cognitively healthy individuals (HIH). The aim of our study was to carefully outline the neuropsychological profile of the patients in order to verify whether hearing loss correlated with deficits in specific cognitive domains. Results: Episodic memory is affected by the presence of hearing loss, while semantic competences, syntactic, and grammar skills seem not to be affected. Furthermore, some audiological features linked to the intelligibility of spoken words can predict the presence of executive dysfunction; the same does not apply to memory impairment. Conclusion: In HIH, executive functions are widely employed in maintaining an acceptable level of comprehension of spoken language; consequently, other cognitive domains and instrumental abilities in HIH are not properly supported. Thus, it is arguable that programs of hearing rehabilitation for HIH could restore the allocation of attentional resources to the functioning of other cognitive domains.